1983
DOI: 10.1002/cpa.3160360204
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic evaluation of certain markov process expectations for large time. IV

Abstract: In this paper we extend our asymptotic results [l], [2] to a more general setting. Let R be a space of functions w (. ) on -00 < t < 00 with values in a Polish space X. We assume R consists of functions with discontinuities only of the first kind, normalized to be right continuous, and with convergence induced by the Skorohod topology on bounded intervals. In this case, R is itself a Polish space. Denote by 0: the corresponding space of functions on [t, 00) with values in X.We denote by S S the a-field in R g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
184
0
4

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 371 publications
(194 citation statements)
references
References 6 publications
0
184
0
4
Order By: Relevance
“…In [Var84] (page 34) and [DV76], [DV83] it is shown that the following five conditions imply the LDP upper bound in (2.2):…”
Section: Sufficient Conditions For the Ldp Upper And Lower Boundsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [Var84] (page 34) and [DV76], [DV83] it is shown that the following five conditions imply the LDP upper bound in (2.2):…”
Section: Sufficient Conditions For the Ldp Upper And Lower Boundsmentioning
confidence: 99%
“…These two conditions are given in [Var84], [DV83], where the LDP is proved as a corollary of a more general LDP on path space in terms of the entropy function (see Theorem 13.1.31 in [Var84]). These two conditions simplify the more cumbersome conditions for the LDP lower bound given on page 393 in [DV76].…”
Section: Sufficient Conditions For the Ldp Upper And Lower Boundsmentioning
confidence: 99%
“…Note at first LDP for family µ ε (dz) = ν ε ([0, 1], dz) (on the space of probability measures supplied by Levy-Prohorov's metric) proved by Donsker and Varadhan [6], [7], [8], [9] for a wide class of Markov processes ξ ε t = ξ t/ε . Corresponding rate function obeys an invariant form: for any probabilistic measure µ on R…”
Section: ∆ ∈ B(r + ) γ ∈ B(r) (13)mentioning
confidence: 99%
“…In contrast with Freidlin and Wentzell [12], Donsker and Varadhan [6] - [9], Gärtner [13], and Veretennikov [26] - [27], and many others (see e.g. Acosta [1], Dupuis and Elis [5]) our method of proof is based on Puhalskii's theorem [19] - [20] and relies concepts of exponential tightness and LD relative compactness.…”
Section: ∆ ∈ B(r + ) γ ∈ B(r) (13)mentioning
confidence: 99%
“…By Proposition 3.7, there exists Q satisfying Q t = µ t for t = 0, 1 and A + (Q) < +∞. By Lemma 3.4 (3.11b), we have, for any such Q, 19) which is finite. Since the last term in (3.19) is independent on Q (i.e., depends only on (µ 0 , µ 1 )), this result follows from Proposition 3.7.…”
Section: The Kinetic Energies Coincide With the Kullback Entropiesmentioning
confidence: 87%